2020
DOI: 10.1002/jso.26157
|View full text |Cite
|
Sign up to set email alerts
|

Is elevated microsatellite alterations at selected tetranucleotide repeats (EMAST)‐negative/MSI‐high colorectal cancer a distinct subtype of the disease?

Abstract: Background and Objectives: Microsatellite instability (MSI) plays a prognostic and predictive role in colorectal cancer (CRC). Elevated microsatellite alterations at selected tetranucleotide repeats (EMAST), a novel type of MSI, was recently identified. Methods: A retrospective analysis of a prospective cohort database was performed. Patients who attempted curative surgery for MSI-high (MSI-H) CRC and had available testing results of EMAST were included for analysis. The difference in clinical characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…However, our results are in contrast to a study on GC by Fang et al [ 18 ], who showed EMAST positivity in only 59% of MSI‐H tumours and demonstrated genetic differences, such as a higher prevalence of mutations in DNA repair genes and of some clinico‐pathological features between EMAST+/MSI‐H and EMAST−/MSI‐H tumours, and a higher frequency of advanced tumour stages and worse survival in the EMAST−/MSI‐H group. Differences in the mutation pattern of several DNA repair genes, specific oncogenes, and tumour suppressor genes, and differences related to age and prognosis between the MSI‐H tumours with and without EMAST have also been described for patients with colorectal carcinoma [ 19 , 20 ]. In addition, an overlap between EMAST and the MSI‐L phenotype has been demonstrated in colorectal cancer; however, this was not confirmed by our results [ 2 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results are in contrast to a study on GC by Fang et al [ 18 ], who showed EMAST positivity in only 59% of MSI‐H tumours and demonstrated genetic differences, such as a higher prevalence of mutations in DNA repair genes and of some clinico‐pathological features between EMAST+/MSI‐H and EMAST−/MSI‐H tumours, and a higher frequency of advanced tumour stages and worse survival in the EMAST−/MSI‐H group. Differences in the mutation pattern of several DNA repair genes, specific oncogenes, and tumour suppressor genes, and differences related to age and prognosis between the MSI‐H tumours with and without EMAST have also been described for patients with colorectal carcinoma [ 19 , 20 ]. In addition, an overlap between EMAST and the MSI‐L phenotype has been demonstrated in colorectal cancer; however, this was not confirmed by our results [ 2 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…EMAST has been described in several tumour entities including GC, with broad variation in incidence ranging from 8 to 60% in gastrointestinal tumours, which may be related in part to the lack of a standardised definition and marker panels used for the determination of EMAST [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. A partial overlap of EMAST with MSI‐H and also with the MSI‐L phenotype has been reported, and it is not clear if EMAST differentiates MSI‐H tumours into two subgroups with potential consequences for treatment with immune therapy and if EMAST alone represents a unique molecular subclass [ 15 , 17 , 18 , 19 , 20 ]. Furthermore, knowledge about EMAST particularly in GC is limited.…”
Section: Introductionmentioning
confidence: 99%